2013
DOI: 10.1111/iju.12247
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rho‐kinase inhibition on myosin light chain phosphorylation and obstruction‐induced detrusor overactivity

Abstract: Abbreviations & Acronyms DMSO = dimethylsulfoxide DO = detrusor overactivity DSM = detrusor smooth muscle EC50 = half maximal effective concentration GSK = GlaxoSmithKlein IEF = isoelectric focusing OAB = overactive bladder MLC20 = myosin light chain 20 kDa MLCP = myosin light chain phosphatase MYPT1 = myosin phosphatase 1 pBOO = partial bladder outlet obstruction ROK = Rho-kinase SHR = spontaneously hypertensive rats Objectives: To study the relationship between myosin light chain phosphorylation of the detru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Elevations in reactive oxygen species and reactive nitrogen species, and changes in the activity of anti‐oxidant mechanisms are induced by pBOO models . Rho‐kinase inhibitors significantly suppressed the force of the spontaneous contractions …”
Section: Introductionmentioning
confidence: 99%
“…Elevations in reactive oxygen species and reactive nitrogen species, and changes in the activity of anti‐oxidant mechanisms are induced by pBOO models . Rho‐kinase inhibitors significantly suppressed the force of the spontaneous contractions …”
Section: Introductionmentioning
confidence: 99%
“…Among identified mechanisms are neurogenic and myogenic alterations of detrusor contractility, as well as changes in bladder stiffness, and ion channels associated with partial bladder outlet obstruction (PBOO), and other pathological conditions of the urinary bladder [ 3 , 8 - 15 ]. It was previously established that a number of DSM pathologies are linked to the changes in signaling proteins including, but not limited to, protein kinase C (PKC), Rho-associated kinase (ROK), and large conductance Ca 2+ -activated potassium (BK) channels [ 5 , 13 , 16 - 26 ]. Alterations in smooth muscle myosin isoforms from the fast phasic isoform to a more tonic one in PBOO [ 27 , 28 ] is correlated with aberrant calcium signaling [ 29 ], and higher resting levels of myosin light chain phosphorylation (MLCP) associated with bladder overactivity [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was previously established that a number of DSM pathologies are linked to the changes in signaling proteins including, but not limited to, protein kinase C (PKC), Rho-associated kinase (ROK), and large conductance Ca 2+ -activated potassium (BK) channels [ 5 , 13 , 16 - 26 ]. Alterations in smooth muscle myosin isoforms from the fast phasic isoform to a more tonic one in PBOO [ 27 , 28 ] is correlated with aberrant calcium signaling [ 29 ], and higher resting levels of myosin light chain phosphorylation (MLCP) associated with bladder overactivity [ 13 ]. It has also been suggested that overactive bladder associated with hypertrophic changes in the smooth muscle may be due to a switch from M 3 to M 2 muscarinic receptor signaling which tends to show increased sensitivity [ 30 - 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…ROCK over‐expression suggests that ROCK inhibitors, such as Y27632, may potentially be a treatment option for DO, and they have been proposed as a therapy in other disorders associated with smooth muscle dysfunction such as hypertension and atherogenesis and GI tract disorders including: recto‐anal incontinence; Hirschsprung's disease (HPD), and gastro‐oesophageal reflux disease . Recently, the ROCK inhibitors Y27632 and GSK‐576371 have been shown to suppress spontaneous bladder overactivity using a rat model of outflow tract obstruction …”
Section: The Potential Role Of Contractile Proteins In Contributing Tmentioning
confidence: 99%